Web system to improve commercial and human talent management using the Scrum methodology - Caciano Arroyo, Maricielo Estefany (2024)
This study focused on implementing a Web System to develop the management of human and commercial talent in a supermarket, using the Scrum methodology. Sales and human resources systems were integrated to optimize customer perception and economic results, highlighting the effectiveness of Scrum in practical cases, such as the implementation of an online sales system for MSMEs caused by the health crisis caused by the spread of COVID-19. The economic results, supported by key indicators such as NPV, B/C and IRR, strengthened the viability of the project. The system was structured into three Sprints, each focused on specific stages, using the Laravel framework and performance testing with JMeter. Additionally, the development phase included the coding of all planned activities. In conclusion, this system promises to be highly beneficial to improve human and sales talent management. The effectiveness of the implementation is supported by performance testing, demonstrating its ability to handle a considerable volume of requests. Financial feasibility, supported by positive indicators, together with an agile approach, promises to significantly improve the operation and competitiveness of a supermarket.